ПРОБЛЕМИ ІНСТИТУЦІЙНО-ПРАВОВОГО ЗАБЕЗПЕЧЕННЯ АСИСТАНСЬКОЇ ДІЯЛЬНОСТІ НА СТРАХОВОМУ РИНКУ УКРАЇНИ - Кнейслер, Ольга Володимирівна; Камінська, Ольга Михайлівна (Науковий журнал «Світ фінансів», 2017)
Кнейслер О. В., Камінська О. М. Проблеми інституційно-правового забезпечення асистанської діяльності на страховому ринку України. Розглянуто проблеми інституціонального середовища асистанської діяльності на страховому ринку. Охарактеризовано організаційну структуру та інфраструктуру страхового ринку, переваги і недоліки взаємодії між учасниками страхових відносин та асистанськими компаніями. Окреслено напрями удосконалення інституційно-правового забезпечення асистансу в контексті підвищення якості сервісного обслуговування страхувальників у процесі врегулювання страхових випадків. Кнейслер О. В., Каминская О. М. Проблемы институционально-правового обеспечения ассистанской деятельности на страховом рынке Украины. Рассмотрены проблемы институциональной среды ассистанской деятельности на страховом рынке. Охарактеризованы организационная структура и инфраструктура страхового рынка, преимущества и недостатки взаимодействия между участниками страховых отношений и ассистанскими компаниями. Определены направления совершенствования институционально-правового обеспечения ассистанса в контексте повышения качества сервисного обслуживания страхователей в процессе урегулирования страховых случаев. Kneysler O., Kaminska O. Problems of institutional and legal support of asystans on insurance market of Ukraine. Introduction. Market transformation in today’s conditions give rise to problems of institutional support insurance market, require the establishment of theoretical and methodological framework for comprehensive coverage of the characteristics and problem solving interaction between participants of insurance relations with institutions of its infrastructure component in the context of improving the quality of service by providing insured services in the asystans settlement of insurance claims. Purpose. A key objective of this research is to solve the problems of institutional and organizational support asystans of insurance and filing vectors to improve the legal relationship between the parties. Results. The institutional environment of the insurance market covers its elements: institutions, both formal (laws and regulations) and informal (mentality, customs and traditions) rules, and institutional and organizational support of the market (main institutional units - insurers, policyholders and insurance intermediaries and support - public institutions to ensure the availability of these standards for the insurance market, intermediaries serving the insurance business). Advantages and disadvantages of interaction between insurers and asystans companies are defined, and also institutional units, that provide asystans services, proposed institutional and organizational model to provide specialized asystans services on insurance market are offered. Directions improvement asystans legal support of the insurance market are grounded in the context of the contractual relationship between the parties. Conclusion. The study concluded that, firstly, the feasibility promote cooperation asystans insurers and companies, and secondly, we believe that the problem of the legal relationship between the insurer and company-assistance possible through the introduction of a separate section entitled “Organization of asystans on the insurance market” to the Law of Ukraine “On insurance” in order to balance the interests of insurers and policyholders and asystans companies to provide quality and reliable insurance protection, it will contribute the financial stability of citizens.